TrpC5 silencing reduces cell invasion and migration and enhances radiosensitivity in papillary thyroid carcinoma cells - Yang, Jing; Sang, Zijiang; Yang, Haibing; Cao, Lvzhou; Chen, Jinxia; Yang, Jiaxin; Gong, Rixiang; Li, Zhihui; Gong, Yanping (Frontiers in Cell and Developmental Biology, 2026)
IntroductionCarcinoma (PTC) is the most common malignant tumor derived from thyroid follicular cells and represents the most common pathological type of thyroid malignancy. Cancer metastasis and radiosensitivity are important factors that limit the treatment of PTC. This study aimed to investigate the regulatory effects of transient receptor potential channel C5 (TrpC5) on the proliferation, invasion, migration, and radiosensitivity of PTC.MethodsHuman papillary thyroid carcinoma cell lines TPC-1 and B-CPAP were transfected with TrpC5 siRNA, pcDNA-TrpC5, or their corresponding negative control. PTC cells were stimulated by radiotherapy.ResultsThe results showed that TrpC5 silencing weakened the proliferation, invasion, and migration of PTC cells, whereas TrpC5 overexpression promoted these cellular behaviors. Moreover, TrpC5 expression was progressively upregulated in PTC cells following exposure to irradiation (IR). TrpC5 silencing enhanced radiosensitivity of TPC-1 and B-CPAP cells. In addition, TrpC5 silencing enhanced the expression of DNA damage-related proteins p-ATM, p-CHK, and γH2AX in PTC cells under IR treatment. Overall, TrpC5 silencing weakened cell invasion and migration and enhanced the radiosensitivity of PTC cells.ConclusionThese findings suggest that TrpC5 may serve as a potential therapeutic target for PTC and warrant further investigation in vivo.